ICT Update 78: Building resilience for family farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2014)
ICT4Ag is a bimonthly printed and on-line magazine (http://ictupdate.cta.int) and an accompanying e-mail newsletter published by CTA. This issue focuses on building resilience for family farming.